Suggestions on the Development of Small and Medium-Sized Science and Technology Enterprises - Chen, Ying (International Journal of Management and Education in Human Development, 2022)
With the help of national favorable policies and combined with the characteristics of scientific and technological small and medium-sized enterprises, this paper analyzes that under the background of the continuous spread of the epidemic, China's economic development has been impacted, and some traditional industries have been greatly impacted, but some scientific and technological small and medium-sized enterprises have grown against the trend, showing strong adaptability and pressure resistance, The reason for providing strong support for comprehensively promoting epidemic prevention and control and economic development is that a number of scientific and technological small and medium-sized enterprises are good at seizing opportunities, have the courage to innovate, and embark on the high-quality development path of "specialization, innovation, characteristics, and refinement".